A multicenter, double-blind, randomized, placebo-controlled trial to evaluate the effect of consuming Growing Up Milk "Lite" on body composition in children aged 12–23 mo. Issue 3 (4th March 2019) - Wall, Clare R; Hill, Rebecca J; Lovell, Amy L; Matsuyama, Misa; Milne, Tania; Grant, Cameron C; Jiang, Yannan; Chen, Rachel X; Wouldes, Trecia A; Davies, Peter S W
ABSTRACT: Background: Growing Up Milk (GUM) was developed to assist young children in meeting their nutritional requirements during the second year of life. However, there is limited evidence that GUM improves nutritional status and growth in young children. Objectives: To evaluate the effect of consuming Growing Up Milk "Lite" (GUMLi) (reduced protein with synbiotics and micronutrients added) compared with standard cow milk as part of a whole diet for 1 y on body composition at 2 y of age. Methods: GUMLi Trial was a multicenter, double-blind, randomized placebo-controlled trial conducted in Auckland and Brisbane. Healthy 1-y-olds were recruited and randomly assigned to receive either GUMLi or standard cow milk for 12 mo as part of a whole diet. The primary outcome was percentage body fat at 2 y of age measured by bioelectrical impedance. All regression models adjusted for baseline outcome and study center. Results: 160 children (80 per arm) were randomly assigned, and 134 (67 per arm) were included in the modified intention-to-treat analyses. The mean percentage body fat at 12 mo was 23.3% (SD 7.9) in the GUMLi group and 25.7% (SD 7.2) in the cow milk group. After adjusting for baseline outcome and study location, the estimated mean difference in percentage body fat between the intervention and control at 12 mo was −2.19% (95% CI: −4.24, −0.15; P  = 0.036). Per-protocol analysis showed a similar effect (mean difference: −2.09%; 95% CI: −4.16, −0.03; P  = 0.047). Both fat mass and the fat mass index were significantly lower in the GUMLi group at 12 mo than in the cow milk group. Conclusions: At 2 y of age, children who consumed a GUM with a lower protein content than cow milk over 12 mo had a lower percentage of body fat. This trial was registered at the Australian New Zealand Clinical Trials Registry as ACTRN12614000918628.